CHANGING GLOBAL ORDER AND POWER REALIGNMENTS IN SOUTHWEST ASIA (ECO REGION) (Margalla Papers, 2022)
The global political and economic system is undergoing radical transformations, which might not be as obvious, but they are fast changing the existing global order. The weakening of US global hegemony, the gain of Chinese economic might and its increasing influence, the establishment of right-wing populist governments across the world, the prolonged conflicts in the Middle East, the NATO withdrawal from Afghanistan, and the recent Ukraine crisis have caused governments to re-assess their foreign policy priorities and to realign themselves in the changing global order. For Russia and China, the emerging new global order should be based on multipolarity and allowed to be developed in different ways. The region of Southwest Asia, as a subset of the international system, is restructuring and realigning itself with the changing geopolitical realities to bring coherence and stability within and across the region. This paper argues that the region's geostrategic importance is instrumental in facilitating the emergence of multipolar global order. Moreover, the new political arrangements also allow the regional states to look beyond western dominance and realign themselves for greater cooperation and stability. There have been predictions that the ECO region could become a centre of global power struggle and play a key role in transforming the global order from unipolar to multipolar.  Bibliography EntryKhan, Ayesha. 2022. "Changing Global Order and Power Realignments in Southwest Asia (ECO Region)." Margalla Papers 26 (1): 61-73.